The secret of life - McAuley, Paul. (London Tor Science Fiction, 2001)
2026: Something is growing in the Pacific Ocean, a strange fungus-like organism that may threaten our entire food chain. Christened "the slick," the bizarre phenomenon is quickly the subject of intense, top-secret analysis-which rapidly reveals that it contains DNA unlike that of any other life on the planet. Where is it from? A Chinese mission to Mars is rumored to have discovered life beneath the Martian icecap, but the Chinese aren't talking. Dr. Mariella Anders is recruited by NASA to join an urgent mission to the Red Planet to find out. Brilliant and committed to science, Mariella wants only the truth, but others' motives are less noble. Faced with corporations, activist groups, and superpowers, each with their own secret agendas, Mariella is on a perilous quest for knowledge. . .and she's about the discover the high price of truth.